Solid-state fermentation of oil palm frond petiole for lignin peroxidase and xylanase-rich cocktail production - Mohamad Ikubar, Mohamed Roslan; Abdul Manan, Musaalbakri; Md. Salleh, Madihah; Yahya, Adibah (3 Biotech, 2018)
In current practice, oil palm frond leaflets and stems are re-used for soil nutrient recycling, while the petioles are typically burned. Frond petioles have high commercialization value, attributed to high lignocellulose fiber content and abundant of juice containing free reducing sugars. Pressed petiole fiber is the subject of interest in this study for the production of lignocellulolytic enzyme. The initial characterization showed the combination of 0.125 mm frond particle size and 60% moisture content provided a surface area of 42.3 m 2 /g, porosity of 12.8%, and density of 1.2 g/cm 3 , which facilitated fungal solid-state fermentation. Among the several species of Aspergillus and Trichoderma tested, Aspergillus awamori MMS4 yielded the highest xylanase (109 IU/g) and cellulase (12 IU/g), while Trichoderma virens UKM1 yielded the highest lignin peroxidase (222 IU/g). Crude enzyme cocktail also contained various sugar residues, mainly glucose and xylose (0.1–0.4 g/L), from the hydrolysis of cellulose and hemicellulose. FT-IR analysis of the fermented petioles observed reduction in cellulose crystallinity ( I 900/1098 ), cellulose–lignin ( I 900/1511 ), and lignin–hemicellulose ( I 1511/1738 ) linkages. The study demonstrated successful bioconversion of chemically untreated frond petioles into lignin peroxidase and xylanase-rich enzyme cocktail under SSF condition.